Triterpene esters from Uncaria rhynchophylla hooks as potent HIV-1 protease inhibitors and their molecular docking study - JiSuk Lee (Scientific Reports)
Abstract Despite significant advancements with combination anti-retroviral agents, eradicating human immunodeficiency virus (HIV) remains a challenge due to adverse effects, adherence issues, and emerging viral resistance to existing therapies. This underscores the urgent need for safer, more effective drugs to combat resistant strains and advance acquired immunodeficiency syndrome (AIDS) therapeutics. Eight triterpene esters (1–8) were identified from Uncaria rhynchophylla hooks. These compounds exhibited potent inhibition of HIV-1 protease (PR), one of the essential enzymes in the virus’s life cycle, with 3β-hydroxy-27-p-Z-coumaroyloxyurs-12-en-28-oic acid (8) showing the most potent inhibitory activity. Structure–activity relationship (SAR) analysis highlighted the importance of the ursane moiety, cis configuration, and p-coumaroyloxy group for inhibitory activity. In silico docking result of triterpene ester 8 elucidated conventional hydrogen bonding with specific amino acid residues—Asp29B, Lys45B, and Asn25A—interacting with the aromatic hydroxyl group at position 7′ and the carboxylic acid at position 28. Additionally, these interactions occur via π–anion and π–alkyl and alkyl hydrophobic interactions, which are responsible for the compound’s mode of action. These molecular docking studies strongly confirmed an excellent SAR. The study suggests that triterpene esters from U. rhynchophylla could represent a new class of potent HIV-1 PR inhibitors with less toxicity, suitable for combination antiretroviral therapy for AIDS.